Interplay between protein carbonylation and nitrosylation in plants. Issue 3 (29th November 2012) - Lounifi, Imen; Arc, Erwann; Molassiotis, Athanassios; Job, Dominique; Rajjou, Loïc; Tanou, Georgia; Dunn, Michael J.
<x xml:space="preserve">Abstract</x> ROS and reactive nitrogen species (RNS) are key regulators of redox homeostasis in living organisms including plants. As control of redox homeostasis plays a central function in plant biology, redox proteomics could help in characterizing the potential roles played by ROS/RNS‐induced posttranslational modification in plant cells. In this review, we focus on two posttranslational modifications: protein carbonylation (a marker of protein oxidation) and protein S‐nitrosylation, both of which having recently emerged as important regulatory mechanisms during numerous fundamental biological processes. Here, we describe the recent progress in proteomic analysis of carbonylated and nitrosylated proteins and highlight the achievements made in understanding the physiological basis of these oxy/nitro modifications in plants. In addition, we document the existence of a relationship between ROS‐based carbonylation and RNS‐based nitrosylation thus supporting the finding that crosstalk between cellular signaling stress pathways induced by ROS and RNS could be mediated by specific protein modifications.